Permeating with Christian Values: Sri Lankan Experience of Cities and City Life - Paul Rohan, J.C. (Pontifical Catholic University of Paraná (PUCPR), 2022)
From its Latin root, ‘city’ (civitas) is closely associated with civilization (civilis) where city life is equated with civilized life. Unfortunately, city life is considered precarious for humanity today. The Bible too is not very positive about cities. Sodom and Gomorrah came under the wrath of Yahweh. Jerusalem lost its divine protection when it became a great city. Jesus condemned the cities of his time, namely, Chorazin, Bethsaida and Capernaum. This shows that though cities and city life mark the growth of humankind, they also represent the decadence of human civilization. Sri Lankan cities are not exceptional to this fact. The dissolution of the spiritual wellbeing bequeathed from the world religious traditions is obvious in them. This paper, along with the positive effects, analyses in detail the severe negative effects of Sri Lankan city life from a Christian perspective. In a caste based and gender biased background of Sri Lanka social and gender discrimination are very much less in its cities. However, marketisation of life and cut-throat competitions are some of the ruthless negative effects that occupy the prime concern against the background of Christian values. The hypothesis is that though the cities empower life with many facilities, they have reduced the human being to be a material commodity. This paper, therefore studies the ways how Christianity, in terms of its faith, beliefs and practices could mediate hope to the negative issues of urbanity. Application of the Christian values of equality, individual dignity and rights, and non- exclusion become the purpose of studying Sri Lankan city life in the terrains of public theology.